Analysis of Brand Image Strategy to Enhance Purchase Interest in Culinary Products - Azzahara, Revika Viola; Yafiz, Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
One of the marketing strategies that need to be built by business actors is through marketing communications. One way to manage consumers and build consumer loyalty with brand image. This study aims to find out how the right brand image strategy is to increase interest in buying culinary products, especially in the city of Medan, and link this view with Islamic law. In this study, authors used a qualitative descriptive method with data collection techniques using observation and literature study, which is a data collection activity by conducting research through previous journals with environmental conditions of research objects that support research activities, so that a clear picture is obtained. about the condition of the research object. From this research it is known that the strategy to have a strong brand of culinary products is in five ways, namely: 1). Conduct brand assessment; 2) Develop a brand promise; 3) Create a brand blueprint; 4) Cultivate brand; 5) Increase brand advantage. This strategy is in line with business principles in Islam put forward by Hermawan Kartajaya who highly upholds consumer satisfaction, of course, based on Islamic law which consists of 10 principles that are all related to brand image strengthening strategies. With the characteristics of the Medan community that are diverse and dominated by nomads, the brand image strategy that is suitable for Medan City is a product image that can be accepted by all groups and certainly does not deviate from the rules or norms in society that are in accordance with current developments. ​